Effectiveness Of Burn Wound Healing From J ackfruit Leaf Ethanol Extract (Artocarpus heterophyllus L.) On Male White Rats (Rattus norvegicus) - Maria Erista Magdalena; Sri Yolandari; Suparman Supardi (International Journal of Multidisciplinary Learners, 2024)
Burns are tissue injuries that often occur due to contact with heat sources, chemicals, or radiation, and can lead to high morbidity and mortality rates. The healing process for burns typically requires a long time and often involves the use of chemicals that pose health risks. Therefore, safer and more effective treatment alternatives are needed. Ethanol extract of jackfruit leaves (Artocarpus heterophyllus L.) is known to contain active compounds such as flavonoids, tannins, and saponins, which have the potential to act as wound healing agents due to their anti-inflammatory and antibacterial properties. This study aims to evaluate the effectiveness of ethanol extract of jackfruit leaves in accelerating the healing of burns in male white rats (Rattus norvegicus). This research employed an experimental method with five treatment groups of varying extract concentrations, as well as positive and negative controls. According to the findings, a 3% extract concentration had the greatest impact on wound healing, which was similar to the positive control that used brand X ointment. ANOVA statistical analysis supported the substantial differences between the treatment groups, suggesting that jackfruit leaf ethanol extract is a useful burn therapy. In conclusion, jackfruit leaf ethanol extract has the potential to be a safe and efficient burn therapy substitute. It merits more research and development for clinical use.